PENGARUH DUKUNGAN ORANG TUA DAN WAKTU BELAJAR TERHDAP PENCAPAIAN KOGNITIF SISWA KELAS IV PADA GUGUS I CAKRANEGARA - Dwi Febbia, Putri; Siti Istinigsih; Syarifuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of parental support and study time on the cognitive achievement of fourth-grade students in Cluster I of Cakranegara. This study employed a quantitative approach with an associative research type and an ex post facto design in the form of correlational research, using proportional random sampling as the sampling technique. Data were collected through questionnaires and documentation, while data analysis was conducted using multiple linear regression, t-test, and F-test. The results showed that partially, parental support had a significant effect on students’ cognitive achievement with a t-value of -3.121 and a significance value of 0.002 < 0.05, while study time also had a significant effect with a t-value of 3.543 and a significance value of 0.001 < 0.05. Simultaneously, the F-test results showed an F-value of 9.693 with a significance value of 0.000 < 0.05, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Therefore, it can be concluded that parental support and study time have a significant effect on the cognitive achievement of fourth-grade students in Cluster I of Cakranegara.